Global Citizenship in the Context of Globalisation: Realising Social Responsibility in the Digital Era - Sakdiah, Halimaton Aton; Putra, Irwan; Ali, Hasbi (Universitas Negeri Gorontalo, 2025)
This research aims to analyse how global citizenship can be realised through social responsibility in the digital era by emphasising the importance of digital literacy as a basic skill that supports global citizens' awareness and participation. The method used is a qualitative approach through literature study, by reviewing various scientific literature, articles, and current reports relevant to the themes of globalisation, global citizenship, and digital literacy. The results show that strong digital literacy not only improves an individual's ability to access and evaluate information, but also strengthens ethical awareness and the ability to participate in global issues critically and responsibly. Individuals with good digital literacy tend to be more sensitive to issues such as climate change, social inequality and human rights, and are able to contribute positively through digital media. It is concluded that global citizenship demands the integration of digital skills and social values, and the need for a transformative educational approach in instilling global awareness. The recommendation from this research is the importance of developing an educational curriculum that combines digital literacy and global citizenship education, in order to form a generation that is not only technologically proficient, but also characterised, critical and responsible as global citizens.